Assessment of endothelial function in patients with nonalcoholic fatty liver disease - YILMAZ, YUSUF (SPRINGER, 2013)
In this study, we aimed to evaluate the endothelial functions in patients with nonalcoholic fatty liver disease (NAFLD). In this observational case-control study, a total of 51 patients with NAFLD in study group and a total of 21 with age- and sex-equivalent individuals in control group were enrolled. In both patients and control groups, levels of asymmetric dimethylarginine (ADMA), systemic endothelial function (brachial artery flow-mediated dilation) (FMD) and carotid artery intima-media thickness (C-IMT) were measured. FMD and C-IMT were evaluated by vascular ultrasound. Plasma levels of ADMA were measured by ELISA. C-IMT was significantly higher in patients with NAFLD group than control group (0.67 +/- A 0.09 vs. 0.52 +/- A 0.11 mm, P < 0.001). The average C-IMT measurements were found in groups of control, simple steatosis, and NAFLD with (borderline and definite) NASH as 0.52 +/- A 0.11, 0.63 +/- A 0.07, and 0.68 +/- A 0.1 mm, respectively. The differences between groups were significant (P < 0.001). Measurement of brachial artery FMD was significantly lower in patients with NAFLD group compared to control group (7.3 +/- A 4.8 vs. 12.5 +/- A 7.1 %, P < 0.001). FMD measurements in groups of control, the simple steatosis, and NAFLD with NASH as 12.5 +/- A 7.1, 9.64 +/- A 6.63, and 7.03 +/- A 4.57 %, respectively, and the differences were statistically significant (P < 0.001). The increase in C-IMT and decrease in FMD was independent from metabolic syndrome and it was also more evident in patients with simple steatosis and NASH compared to control group. There was no significant difference between the control and NAFLD groups in terms of plasma ADMA levels (0.61 +/- A 0.11 vs. 0.69 +/- A 0.37 mu mol/L, P = 0.209). Our data suggested that NAFLD is associated with endothelial dysfunction and increased earlier in patients with atherosclerosis compared to control subjects.
Keywords: Endothelial dysfunction; Carotid artery intima-media thickness; Brachial artery flow-mediated dilatation; Asymmetric dimethylarginine; ASYMMETRIC DIMETHYLARGININE ADMA; INTIMA-MEDIA THICKNESS; CARDIOVASCULAR RISK; METABOLIC SYNDROME; DYSFUNCTION; PLASMA; ARTERY; STEATOHEPATITIS; ADIPONECTIN; HISTOLOGY